CPC-065 How to Assess Medication Adherence Among Patients with Resistant Hypertension Treated with Two Different Pharmacological Intensification Strategies. (12th March 2013) - Beaussier, H; Coudore, F; Bobrie, G; Peyrard, S; Tran, L; Bezie, Y; Azizi, M; Boutouyrie, P
Abstract : Background: Non-adherence to medicines and lifestyle are the main contributors to resistance to antihypertensive treatment (AHT). Various measures to assess medicines adherence (MA) among patients with resistant hypertension (RH) have been proposed but none is fully effective. Purpose: To assess MA with a new scoring system in RH patients included in a randomised controlled trial and the characteristics associated with low MA. Materials and Methods: Patients with RH on 4 week-treatment with irbesartan 300 mg + hydrochlorothiazide 12.5 mg + amlodipine 5 mg, were randomised to either reinforcement of sodium depletion by sequential administration of spironolactone and other diuretics (AB group, n = 82) or reinforcement of renin angiotensin system blockade by sequential administration of ramipril 5–10 mg and bisoprolol 5–10 mg (RB group, n = 82) for 12 weeks. In accordance with the literature, 4 methods were used to evaluate MA: 1/measurement of plasma irbesartan concentration (HPLC); 2/measurement of urinary AcSDKP/creatinine ratio (UR) to evaluate ACE inhibitor exposure; 3/last dose of medicine taken before visit; 4/pill counting (MA ratio = real/theoretical doses taken). One point (+1 point score) was attributed for MA if: Irb >20 ng/ml or UR >4 nmol/mmol or last dose had been taken <24 h before visit or MA ratio >80%. Three MA levels were assigned: low MA (score <2), intermediate MA (score +3), and sufficient MA (score + 4). Results: Only 82 patients were sufficiently adherent: 46 and 36 patients among the AB and RB groups, respectively. 52 had intermediate MA (23 and 29, respectively); 30 had low MA (13 and 17, respectively) (inter-groups difference NS). Patients with low MA were younger than sufficient MA patients (50 ± 11 vs. 56 ± 10 yrs, p < 0.011); no difference was ascribed to gender or dASBP (152 ± 14 vs. 148 ± 12 mmHg, p = 0.16). Other clinical characteristics did not differ except the glomerular filtration rate: lower among adherent patients than low MA patients (95 ± 25 vs. 107 ± 28 ml/min, p < 0.02). Conclusions: We propose a score of 3 MA levels (low, intermediate, sufficient) based on 4 complementary quantitative and qualitative methods. A combination approach is essential to balance imprecision of observed data. There were no differences in major clinical characteristics between groups. Further comparisons into each group of treatment and longer duration of treatment might be necessary to observe a significant differential effect among MA groups. Therapeutic education sessions could be useful for RH patients who undertake complex treatment. No conflict of interest.